Konstruksi Yesus sebagai Anak Allah dalam Teologi Politik - Yohanes Hasiholan Tampubolon; Dreitsohn Franklyn Purba; Rinaldo A.P. Bettay (PASCA : Jurnal Teologi dan Pendidikan Agama Kristen, 2023)
The meaning of "son of God" is often colored by the theological-philosophical descriptions of post-first century theologians. Through this research, the author will explain the concept of "son of God" in the light of the socio-political situation of the first century where the writing of the book of Romans was carried out. Through the biblical exegesis method, the author emphasizes that the concept of "son of God" in Romans 1:3-4 has relevance for the political role of today's readers. The writer finds that the political relevance related to the meaning of the child of God is that the Church is not always in an obedient position, but can be critical; Even though Paul was critical, he still did not encourage the congregation to act against them with violence; Paul's critical attitude towards the state was in the realm of ideology; Jesus is the Son of God, ideally, an Example for Rulers. Through this paper, we will bring an alternative interpretation of the meaning of "son of God" in the current context.